Can Alumnus of English Learner Remember Their English? A Case Study on Fldi Nurul Jadid - Achmad Naufal Irsyadi; Althafurrahman Althafurrahman (RETORIKA: Jurnal Ilmu Bahasa, 2019)
This research attempts to explain a phenomenon that occurs psycholinguistics in everyday life, especially in the environment of English learner. The basic assumption is the English learner faces difficulties in producing English sentence orally, so that problems such as forgetting the language in producing the language could happen. The research will involve alumnus of English learners of English Language Institute LPBA Nurul Jadid domiciled in Jember. From the observations, there are approximately 86.7% of respondents admitted that they often run into problems in the production of English as second language. There are 60% of respondents admitted that they had experienced of forgetfulness in the production of English as second language in the level of the sentence. 80% in the level of words, 78.6% in the level of expression, and 71.4% in the level of the phrase. This study shows that forgetfulness in producing English has a neural factor that is the Short term Memory (STM) of the alumnus. They have difficulty in recalling the vocabularies in English.